1996
DOI: 10.1128/jb.178.22.6475-6478.1996
|View full text |Cite
|
Sign up to set email alerts
|

Deletion mapping of the sites on the HtrI transducer for sensory rhodopsin I interaction

Abstract: The phototaxis receptor sensory rhodopsin I (SRI) transmits signals through a membrane-bound transducer protein, HtrI. The genes for the receptor and transducer, sopI and htrI, respectively, are normally cotranscribed; however, previous work has established that fully functional interacting proteins are produced when htrI is expressed from the chromosome and sopI is expressed from a different promoter on a plasmid. In this report we show that in the membrane, concentrations of SRI from plasmid expression of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 23 publications
5
35
0
Order By: Relevance
“…This is a much shorter region than the 94 cytoplasmic residues found sufficient in a previous study (24), the key advantage here being the use of SRI-HtrI fusions that allowed much shorter HtrI fragments to be stabilized. (ii) The final 5 residues (62-66) are nearly completely responsible for the closure effect, and (iii) channel closure by this membrane-proximal domain requires the membrane-embedded domain of HtrI, which alone interacts with SRI altering to a small extent its properties, but without significantly closing the channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a much shorter region than the 94 cytoplasmic residues found sufficient in a previous study (24), the key advantage here being the use of SRI-HtrI fusions that allowed much shorter HtrI fragments to be stabilized. (ii) The final 5 residues (62-66) are nearly completely responsible for the closure effect, and (iii) channel closure by this membrane-proximal domain requires the membrane-embedded domain of HtrI, which alone interacts with SRI altering to a small extent its properties, but without significantly closing the channel.…”
Section: Discussionmentioning
confidence: 99%
“…C-terminal deletion analysis showed that the N-terminal 147 residues of HtrI (full-length HtrI contains 536 residues) are sufficient to close the channel of SRI in the native H. salinarum membrane (24). Shorter fragments either were not expressed well and/or folded improperly in the H. salinarum cell.…”
mentioning
confidence: 99%
“…Ϫ lacking the four archaeal rhodopsins (BR, HR, SRI, and SRII) as well as the two transducer proteins (HtrI and HtrII) was used for transformation (18) according to the protocol described previously (19). To obtain a high expression level, the stronger bop promoter was used instead of the native promoter (19).…”
Section: Strain For Transformation-h Salinarum Strain Pho81wrmentioning
confidence: 99%
“…In ninaA mutants, rhodopsin is retained within the endoplasmic reticulum, and its levels are reduced by more than 100-fold (48). The membrane insertion of sensory rhodopsin I (SopI) found in H. salinarum is dependent on a chaperon-like function of its signal transducer, HtrI, which facilitates membrane insertion and protein folding of SopI (49). It was also shown that the chaperonin GroEL can promote post-translational membrane insertion of the multispanning membrane protein lactose permease in vitro (50).…”
Section: Figmentioning
confidence: 99%